Portal do egresso: proposta para acompanhamento de egressos do mestrado profissional em Gestão nas Organizações Aprendentes - Souza, Mariana Celeste Carvalho da Silva de (2022)
The main objective of this technical report is to create, in the form of a prototype, the MPGOA Graduate Portal. Graduate school courses in Brazil are submitted to a Quadrennial Evaluation promoted by CAPES and, thus, must comply with the items demanded in Evaluation Forms. Besides other questions, these items also deal with subjects such as course self-evaluation, graduates follow-up and course visibility in communication media, which are the topics approached in this report. In order to do that, the following concepts are presented: learning, both on individual and organizational level; learning organizations; CAPES evaluation form; self-evaluation; graduates follow-up; internet in Brazil; Digital Information and Communication Technologies. The construction of the Graduate Portal used steps of the Design Thinking process, a methodology applied when prototypes are intended to be created. Questionnaires were also applied with MPGOA’s graduates, whose answers, besides being important elements in the conception of the Portal, also helped the brief data analysis presented here. As a result, the report presents a hyperlink to the MPGOA Graduate Portal, created with Google Sites, conceptually representing the creation of a follow-up mechanism for the graduates from Master’s Program in Learning Organizations Management.